Saving Europe? The unpleasant arithmetic of fiscal austerity in integrated economies - Enrique G. Mendoza; Linda L. Tesar; Jing Zhang (Federal Reserve Bank of Chicago, 2014)
What are the macroeconomic effects of tax adjustments in response to large public debt shocks in highly integrated economies? The answer from standard closed-economy models is deceptive, because they underestimate the elasticity of capital tax revenues and ignore crosscountry spillovers of tax changes. Instead, we examine this issue using a two-country model that matches the observed elasticity of the capital tax base by introducing endogenous capacity utilization and a partial depreciation allowance. Tax hikes have adverse effects on macro aggregates and welfare, and trigger strong cross-country externalities. Quantitative analysis calibrated to European data shows that unilateral capital tax increases cannot restore fiscal solvency, because the dynamic Laffer curve peaks below the required revenue increase. Unilateral labor tax hikes can do it, but have negative output and welfare effects at home and raise welfare and output abroad. Large spillovers also imply that unilateral capital tax hikes are much less costly under autarky than under free trade. Allowing for one-shot Nash tax competition, the model predicts a "race to the bottom" in capital taxes and higher labor taxes. The cooperative equilibrium is preferable, but capital (labor) taxes are still lower (higher) than initially. Moreover, autarky can produce higher welfare than both Nash and Cooperative equilibria.
Keywords: E61; E62; E66; F34; F42; F62; 330; European debt crisis; tax competition; capacity utilization; fiscal austerity